Numerical Calculation of Transient Thermal Characteristics in Gas-Insulated Transmission Lines - Li Hongtao Li Hongtao; Shu Naiqiu; Li Ling Li Ling; Wu Xiaowen Wu Xiaowen (Universitas Ahmad Dahlan, 2013)
For further knowledge of the thermal characteristics in gas-insulated transmission lines (GILs) installed above ground, a finite-element model of coupling fluid field and thermal field is established, in which the corresponding assumptions and boundary conditions are given. Transient temperature rise processes of the GIL under the conditions of variable ambient temperature, wind velocity and solar radiation are respectively investigated. Equivalent of surface convective heat transfer coefficient and heat flux boundary conditions are updated in the analysis process. Unlike the traditional finite element method (FEM), the variability of the thermal properties with temperature is considered. The calculation results are validated by the tests results reported in the literature. The conclusion provides method and theory basis for the knowledge of transient temperature rise characteristics of GILs in open environment.